Limitation of solid-reaction technique in a controlled experiment: Characterization of polycrystalline LaCe0·9Th0.1CuOy compound - Moses Eterigho Emetere (Kuwait Journal of Science)
Solid-state reactions are the most prominent method to synthesize compounds in physics, chemistry, and material science because of their simplicity to scale up or down. Its uneven chemical reactions result in wide variances in the optical and microstructural properties of the material. There is therefore a need to adopt computational techniques to filter out anomalies. This research considers the polycrystalline growth of LaCe0·9Th0.1CuOy via the solid-state reaction. Its chemical and morphology properties were investigated by considering the phasal change and orientation of LaCeTh0·1CuOy. The material was characterized using scanning electron microscopy (SEM), transition electron microscopy (TEM), and X-ray diffractometry (XRD). The structural formulations of the generated phases have a unique combination of phases that yields new electronic properties. It was observed through the surface and bulk scans that the LaCeTh0.1CuOy has approximately 72% homogeneity and about 28% heterogeneity. Copper, oxygen, and cerium were observed to influence the surface morphology of LaCeTh0·1CuOy. Hence, aside from the outer and inner CuO2 planes that possess four and five coordination numbers, it could be inferred that the ratio of structural impact of the inner and outer CuO2 planes in LaCeTh0.1CuOy is 5:1. This anomaly may be responsible for the unresolved mechanism in a few solid-state devices or compounds.